Incidents and sanctioning of illegal and dangerous ruck cleanouts during the 2015 to 2019 under 18 Craven Week Rugby Tournament - Kruger, Stephanie Helen (Stellenbosch : Stellenbosch University, 2021)
Thesis (M Sport Sc)--Stellenbosch University, 2021.